Bridging the urban–rural gap in facilitating Local Economic Development: The case study of uMgungundlovu District Municipality in KwaZulu–Natal, South Africa. (June 2021) - Makhaye, Ayanda C; Subban, Mogie; Gerwel Proches, Cecile N
Municipalities are faced with poverty, unemployment and inequality, to the detriment of growth and development. As specified in the South African Constitution (1996), municipalities are obligated to advance Local Economic Development (LED). Municipalities cannot accomplish this task alone; therefore, participation of all stakeholders is required. The aim of this study is to investigate bridging the urban–rural gap in facilitating LED within uMgungundlovu District Municipality in KwaZulu–Natal in understanding this phenomenon. The district is made up of seven urban and rural local municipalities. Using a qualitative research method through an interpretive paradigm, data were collected from purposely selected participants through in-depth open-ended interviews. Collected data were analysed through induction using thematic and content analysis. Results revealed gaps in understanding LED planning, facilitation and implementation, including gaps in resource planning and provision. The study revealed numerous stakeholders were relevant in facilitating LED within the District. It is recommended that the District improves rural service delivery and infrastructure provision enabling access of opportunities and creating platforms for stakeholder engagement, with inclusion of traditional leaders driving LED facilitation. Priority areas for enhancing LED initiatives are suggested, with LED viewed as a good initiative in achieving sustainable development in district municipalities.